2018
DOI: 10.1016/j.bpj.2018.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Dual Role of the C-Terminal Domain in Osmosensing by Bacterial Osmolyte Transporter ProP

Abstract: ProP is a member of the major facilitator superfamily, a proton-osmolyte symporter, and an osmosensing transporter. ProP proteins share extended cytoplasmic carboxyl terminal domains (CTDs) implicated in osmosensing. The CTDs of the best characterized, group A ProP orthologs, terminate in sequences that form intermolecular, antiparallel a-helical coiled coils (e.g., ProPEc, from Escherichia coli). Group B orthologs lack that feature (e.g., ProPXc, from Xanthomonas campestris). ProPXc was expressed and characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(53 citation statements)
references
References 82 publications
(133 reference statements)
2
51
0
Order By: Relevance
“…The osmoadaptive mechanism that protects respiration may be related to the mechanism by which osmotic upshifts inhibit respiration. By measuring DPH fluorescence anisotropy, Cul-ham et al (5) showed that osmotic upshifts decreased the membrane fluidity of liposomes comprised of E. coli phospholipid. Such a decrease may render the intramembrane diffusion of electron carriers rate-limiting for respiration, and osmotic adaptation of the respiratory system may be designed to address that limitation.…”
Section: Q8-independent Protection Of Respiration In E Colimentioning
confidence: 99%
See 3 more Smart Citations
“…The osmoadaptive mechanism that protects respiration may be related to the mechanism by which osmotic upshifts inhibit respiration. By measuring DPH fluorescence anisotropy, Cul-ham et al (5) showed that osmotic upshifts decreased the membrane fluidity of liposomes comprised of E. coli phospholipid. Such a decrease may render the intramembrane diffusion of electron carriers rate-limiting for respiration, and osmotic adaptation of the respiratory system may be designed to address that limitation.…”
Section: Q8-independent Protection Of Respiration In E Colimentioning
confidence: 99%
“…Following extrusion, liposomes (in rehydration buffer) were supplemented with 0.06% DPH (w/w, relative to lipid; ϳ0.2 mol%) (Molecular Probes, Inc., Eugene, OR) and incubated for 18 -20 h in the dark at room temperature. Fluorescence measurements were performed at the specified temperature using a PTI QuantaMaster QM-8 steady state fluorimeter as described (5). Duplicate measurements from two independent experiments were combined and analyzed as described (5).…”
Section: Diphenylhexatriene Fluorescence Anisotropymentioning
confidence: 99%
See 2 more Smart Citations
“…Escherichia coli possesses two osmotically regulated uptake systems for a variety of compatible solutes: the proton-solute symporter ProP, a member of the major facilitator superfamily (MFS) and the ABC-type (ATP-binding cassette) transporter ProU (Lucht and Bremer, 1994; Wood et al, 2001). Both transporters can also serve as uptake systems for ectoine and 5-hydroxyectoine (Jebbar et al, 1992; Czech et al, 2016; Culham et al, 2018). For our studies on the osmostress protective properties of homoectoine (Nagata, 2001), we used the well-known E. coli K-12 laboratory strain MG1655 (Blattner et al, 1997) and an isogenic set of mutant strains derived from MG1655 with defects in either ProP or ProU, or in both transport systems (Supplementary Table S1).…”
Section: Resultsmentioning
confidence: 99%